Multi-species bacterial biofilm and intracellular infection in otitis media - Thornton Ruth B; Rigby Paul J; Wiertsema Selma P; Filion Pierre; Langlands Jennifer; Coates Harvey L; Vijayasekaran Shyan; Keil Anthony D; Richmond Peter C (BMC, 2011)
Abstract Background Bacteria which are metabolically active yet unable to be cultured and eradicated by antibiotic treatment are present in the middle ear effusion of children with chronic otitis media with effusion (COME) and recurrent acute otitis media (rAOM). These observations are suggestive of biofilm presence or intracellular sequestration of bacteria and may play a role in OM pathogenesis. The aim of this project is to provide evidence for the presence of otopathogenic bacteria intracellularly or within biofilm in the middle ear mucosa of children with COME or rAOM. Methods Middle ear mucosal biopsies from 20 children with COME or rAOM were examined for otopathogenic bacteria (either in biofilm or located intracellularly) using transmission electron microscopy (TEM) or species specific fluorescent in situ hybridisation (FISH) and confocal laser scanning microscopy (CLSM). One healthy control biopsy from a child undergoing cochlear implant surgery was also examined. Results No bacteria were observed in the healthy control sample. In 2 of the 3 biopsies imaged using TEM, bacteria were observed in mucus containing vacuoles within epithelial cells. Bacterial species within these could not be identified and biofilm was not observed. Using FISH with CLSM, bacteria were seen in 15 of the 17 otitis media mucosal specimens. In this group, 11 (65%) of the 17 middle ear mucosal biopsies showed evidence of bacterial biofilm and 12 demonstrated intracellular bacteria. 52% of biopsies were positive for both biofilm and intracellular bacteria. At least one otopathogen was identified in 13 of the 15 samples where bacteria were present. No differences were observed between biopsies from children with COME and those with rAOM. Conclusion Using FISH and CLSM, bacterial biofilm and intracellular infection with known otopathogens are demonstrated on/in the middle ear mucosa of children with COME and/or rAOM. While their role in disease pathogenesis remains to be determined, this previously undescribed infection pattern may help explain the ineffectiveness of current treatment strategies at preventing or resolving COME or rAOM.